Environmental Impact on Energy Production (The case of VRA-Ghana) - Gabienu, Francis (My University, 2019)
In this research, the discussion is centered on the construction of the Akosombo dam on the Volta River by the Volta River Authority (VRA) of Ghana and its impacts on the immediate environment and the ecosystem, the effect on the people living in the catch-ment area and their sources of livelihood. In terms of both its operations and expansion in the power production activities, the ini-tial project was only the hydro-power generation, which later on expanded to include a number of other sources of energy production. This expansion covers a period of ap-proximately six decades, from 1963 to 2014. The review of literature consists of five areas such as, Important Environmental Considerations catered for by the Volta River Authority (VRA), Environmental Concerns associated with the individual phases of the project, Steps lacking in the implementation method with respect to the Environmental concerns, Socio-economic cost of the Environmental concerns associated with the project and Remedial Strategies with their effectiveness. The research methodology consists of five main headings such as Research Design, Data Collection, Sample and Population, Analysis and Limitations of the study. This research is a mixed-method study because, while the literature constitutes the basis for both the discussion and the main argument which is qualitative, the provision of an empirical evidence base is also quantitative. The findings are divided into three main areas which are as follows; Presentation of the systematic literature review, Analysis towards classification of the research objectives and Analysis of findings in the light of the two main Environmental Theories.
Keywords: Energy; Environment; Production; Impact; Volta River Authority; fi=Tuotantotalous|en=Industrial Management|